Travel mode choice of shopping centre customers in Germany: spatial and sociodemographic structures - Michel, David W.; Scheiner, Joachim (ERDKUNDE, 2016)
Shopping trips continue to be an important topic in spatial development and spatial planning. This paper studies the travel mode choice of customers in 17 German shopping centres. Secondary data collected in customer surveys are used to analyse associations between the location and accessibility of shopping centres and customers’ travel modes. Associations with customers’ sociodemographic attributes are considered simultaneously using a multinomial logit regression model. The results show that shopping centre location, the urban environment at the destination (shopping centre) and the origin of trips (typically the customers’ places of residence) have considerable effects on mode use. What is more, the effects of social roles (gender, household size), resources (income), shopping behaviour (frequency of visit), and spatial context suggest that users of public modes and non-motorised modes differ from car users in quite similar ways.